Synthesis of novel 9R/S-acyloxy derivatives of cinchonidine and cinchonine as insecticidal agents. Issue 2 (1st February 2021) - Che, Zhi-Ping; Yang, Jin-Ming; Zhang, Song; Sun, Di; Tian, Yue-E; Liu, Sheng-Ming; Lin, Xiao-Min; Jiang, Jia; Chen, Gen-Qiang
Abstract: Endeavor to discover biorational natural products-based insecticides, two series (27) of novel 9 R/S -acyloxy derivatives of cinchonidine and cinchonine were prepared and assessed for their insecticidal activity against Mythimna separata in vivo by the leaf-dipping method at 1 mg/mL. Among all the compounds, especially derivatives 6l and 6o exhibited the best insecticidal activity with final mortality rates of 75.0% and 71.4%, respectively. Overall, a free 9-hydroxyl group is not a prerequisite for insecticidal activity and C9-substitution is well tolerated; the configuration of C8/9 position is important for insecticidal activity, and 9 S -configuration is optimal; 6'-OCH3 moiety is not necessary, removal of it is also acceptable.